(untitled) (Revista Contexto & Saúde, 2022)
Oxidative stress is the result of reactive oxygen species (ROS) overproduction and/or a decline in antioxidant defense mechanisms. Oxidative stress can be marked by deleterious effects on DNA, proteins, and lipids structure, changing cell homeostasis, and contributing to the development of metabolic diseases as type two diabetes (T2D), characterized mainly by insulin resistance in several tissues, as skeletal muscle. The T2D development and its complications are related to mitochondrial dysfunction and oxidative stress, as well as pro-inflammatory state and metabolic unbalance. Acute exercise represents a necessary type of challenge to whole-body homeostasis. Therefore, regular exercise (sum of acute exercise challenges) promotes antioxidant, anti-inflammatory, and metabolic adaptations induced by each stress induced by the exercise session, evoking a hormesis effect (from mitochondria to many tissues) that is beneficial for T2D prevention and treatment. Despite of a considerable research information in the field, the characterization of the sources and pathways of ROS generation in T2D and during exercise still a matter for investigation. Therefore, the multifaceted effects of oxidative stress in T2D and the link of exercise in T2D are discussed in this review.